Fatigue Behavior and Lifetime Prediction of Unidirectionally Wire Reinforced Lightweight Metal Matrix Composites1. Issue 6 (7th January 2015) - Merzkirch, Matthias; Hammers, Thilo; Reeb, Andreas; Schwind, Thomas; Riedl, Sascha; Thiel, Leon; Henschel, Alexander; Kerscher, Eberhard; Schulze, Volker; Weidenmann, Kay André
<x xml:space="preserve">Abstract</x> In the field of lightweight construction for transportation means, hybrid structures composed of high‐strength and low‐density materials exhibit a high potential for application. The composite extrusion process allows an easy embedding of metallic reinforcements into a multitude of light metal alloys. The current work shows that different metallic wire reinforced light alloys with a content of 11.1 vol% lead to a significant increase in lifetime of different aluminum and magnesium alloys under fully reversed stress controlled fatigue loading. Based on the knowledge of the quasi‐static behavior of the single components and the fatigue behavior of the matrix material, a new lifetime model is used to predict the lifetime for different unidirectionally reinforced material systems.